Progress of radiomics research on white matter hyperintensity lesions - Lin Du; Lieping Wang; Gang Shen; Min Zeng; Desheng Li; Weiguo Li (Frontiers in Neurology)
White matter hyperintensity (WMH) is the core imaging hallmark of cerebral small vessel disease (CSVD). This phenomenon is closely related to nervous system damage, such as cognitive impairment, dementia and increased risk of stroke. However, traditional diagnostic methods have significant limitations in terms of quantitative assessment, analysis of pathological mechanisms, and clinical decision support, which severely restrict their clinical application. Through high-throughput feature extraction and comprehensive analysis of clinical, laboratory, histological, and genomic data, radiomics in its current form can not only achieve the high-precision identification and staging of WMH but also help to reveal its pathological mechanism, which has shown important value in the diagnosis, prognosis, and evaluation of WMH-related diseases. Against this backdrop, we strictly adhered to the norms of systematic literature reviews, conducting a comprehensive and transparent literature search. We also thoroughly reviewed the data using a predefined strategy and strict inclusion/exclusion criteria (detailed in the text). This article systematically reviews the progress of radiomics research in characterizing the pathological mechanism of WMH and in the early identification, classification and prognostic evaluation of related diseases, aiming to provide a theoretical basis and a technical reference for the early identification of high-risk groups, the optimization of diagnosis and treatment decision-making, and the practice of collaborative patient management.